Roaring Rockets - Mitton, Tony and Parker, Ant (London Kingfisher Publication Plc, 1999)
A simple explanation of how space rockets work, where they travel, and what they do.
Include Color Illustrations
Keywords: Rockets (Aeronautics) -- Outer space -- Exploration of outer space -- Manned space flight